Prevence a zvládání pracovních konfliktů - Doležalová, Andrea (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Bakalářská práce analyzuje problémy, které vznikají na pracovišti, v pracovním kolektivu. Analyzuje tedy pracovní konflikty. Obsahuje návrh takové prevence a zvládání konfliktů, který při respektování povede k lepší komunikaci a ke snižování konfliktů v podniku.

This bachelor's thesis analyses problems rising on workplace, in working group. This work analyses working conflicts. It includes the proposal of such prevention and control of conflicts, which close to respecting leads to better communication and to the reduction of conflicts in the company.
Prevention and Control of working Conflicts
Keywords: konflikt; rozpor; pracovní kolektiv; soupeření; spolupráce; osobnost; mobbing; teambuilding; pracovní prostředí; prevence; conflict; variance; working group; rivalry; cooperation; personality; mobbing; teambuilding; working environment; prevention